2019
DOI: 10.1055/s-0039-3401829
|View full text |Cite
|
Sign up to set email alerts
|

Lymphaticovenous Bypass for Immediate Lymphatic Reconstruction in Locoregional Advanced Melanoma Patients

Abstract: Background Extremity lymphedema is a dreaded complication of ilioinguinal or axillary lymphadenectomy. In conventional lymph node dissection, no effort is performed to maintain or reestablish extremity lymphatic circulation. We hypothesized that immediate lymphatic reconstruction (ILR) could be a reproducible procedure to maintain functional lymphatic flow after ilioinguinal and axillary lymphadenectomy in patients with malignant melanoma. This is the first report describing prophylactic ILR in patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…[4][5][6] Therefore, many surgeons began describing this procedure as an immediate lymphatic reconstruction (ILR), rather than preventive or prophylactic. [7][8][9] Boccardo and colleagues' results have been replicated by several retrospective and prospective studies. A 2018 meta-analysis of 4 papers found that patients who underwent upper-or lower-extremity ILR had a relative risk of 0.33 for developing lymphedema when compared to controls (P<0.0001).…”
Section: Classic and Modified Techniques Of Immediate Lymphatic Reconstructionmentioning
confidence: 76%
See 1 more Smart Citation
“…[4][5][6] Therefore, many surgeons began describing this procedure as an immediate lymphatic reconstruction (ILR), rather than preventive or prophylactic. [7][8][9] Boccardo and colleagues' results have been replicated by several retrospective and prospective studies. A 2018 meta-analysis of 4 papers found that patients who underwent upper-or lower-extremity ILR had a relative risk of 0.33 for developing lymphedema when compared to controls (P<0.0001).…”
Section: Classic and Modified Techniques Of Immediate Lymphatic Reconstructionmentioning
confidence: 76%
“…[4][5][6] Therefore, immediate lymphatic reconstruction (ILR) has been adopted by some as an alternative name. [7][8][9] While preliminary results are favorable, concerns exist surrounding scheduling issues, unfavorable proximal lymphovenous pressure gradients, oncologic safety, and anastomotic injury from postoperative radiation. 10 Delayed, distally-based LVA (DD-LVA) is an emerging alternative method that allows surgeons to avoid these issues.…”
Section: Introductionmentioning
confidence: 99%
“…The application of immediate lymphatic bypass has also recently expanded beyond the scope of breast cancer and has been applied to patients undergoing lymphadenectomy for melanoma and gynecologic malignancy [ 21 , 22 , 23 ]. Takeishi et al performed intrapelvic LVA after lymph node dissection for patients with uterine cancer to prevent lower extremity lymphedema [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respectively, these studies have reported lymphedema rates of 4.3% and 4.5% in those undergoing ILR, representing a significant rate reduction when compared to the lymphedema rates in these patients as reported in the literature. 28,29 The results of several other studies investigating ILR at the time of axillary node dissection are outlined in Table 1. They have all shown favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%